Utilization Of Google Class Room In Islamic Religious Education Subjects At Smp Rahmat Islamiyah Medan - Hasrian Rudi Setiawan; Mayurida Mayurida (International Journal Reglement & Society (IJRS), 2022)
his study aims to describe how teachers and students in Islamic religious education learning activities use google classroom as a learning medium. This research is a qualitative descriptive study in class VIII SMP Rahmat Islamiyah Medan. Data collection was carried out using several data collection techniques, including: interviews, observation and documentation studies. The research findings show that the use of google classroom in Islamic religious education learning activities is used as a stone tool by teachers and students in the implementation of distance learning activities. Google classroom is used in distance learning activities, because: 1) google class room provides virtual classrooms; 2) google Classroom has features that make it easier for teachers to provide teaching materials and materials to students; 3) Means of discussion and communication between students and teachers without being limited by space and time; 4) as a tool for teachers in giving assignments and assessments to students.